Strategi Keunggulan Bersaing Perkantoran di Complex Pondok Indah City Jakarta yang di Pengaruhi oleh Inovasi, Kualitas Layanan dan Reputasi yang Berdampak kepada Kinerja Perusahaan - Arnal Hasibuan; Mombang Sihite; Fahruddin Salim (Jurnal Syntax Admiration, 2025)
The increase in good economic growth, especially in Jakarta, makes the property sector committed to developing its company in order to meet the needs of the community not only offices but also combining offices, residences and other activity centers in adjacent areas. This is a step and strategy carried out to increase selling value with an increasingly competitive market. The goal is to provide a space that is able to meet human needs and provide comfort for users. With the above concept, the author conducts research for the purpose of comprehensively exploring and examining data and information related to innovation variables, service quality, and company reputation in the Pondok Indah City Jakarta complex so that the company produces a competitive advantage that can improve company performance.